Allocation of the Right to Tax Income from Digital Intermediary Platforms – Challenges and Possibilities for Taxation in the Jurisdiction of the User - Louise Fjord Kjærsgaard; Peter Koerver Schmidt (Nordic Journal of Commercial Law, 2018)
The authors analyse the current (lack of) possibilities for userjurisdictions to tax the value generated by the increased use of digital intermediary platforms. Focus is on analysing the possibilities for userjurisdictions to tax the remuneration received by a foreign enterprise owning a digital intermediary platform and on disucussing whether the users’ provision of personal data in exchange for access to the platform could be considered a barter transaction for tax purposes in the userjurisdiction. Among other things, it is concluded that user-jurisdictions, pursuant to current international tax treaties, will normally be precluded from taxing the income of foreign platform enterprises, as the platform enterprises are often able to deliver their digital services remotely. Against this background, a number of tax policy challenges and options of relevance for taxing platform enterprises are discussed, in particular the proposed directive on significant digital presence recently put forward by the European Commisssion. It is concluded that the proposal may prove to be an adequate step towards taxation in the userjurisdictions, even though the proposal needs further work in order to become sufficiently clear and targeted and the scope may be limited.